The principle of public faith in the registry today: does it still exist? - Ortega Mejía, Ciro Vladimir (2023)
The principle of public faith in the registry is back on everyone’s lips as a result of the ruling of the third party in good faith of the Peruvian Constitutional Court. Although its constitutionality was reaffirmed, the principle of public faith in the registry underwent a huge change that raises the question: does the principle of public faith in the registry still exist?In this article, the author summarizes the uneven path of the principle of public faith in the registry in Peru and its conception today, recalling its theoretical and practical basis, and criticizes its current conception.